Resistência primária e diversidade genética do vírus da imunideficiência humana (HIV-1), em amostras de pacientes que iniciaram tratamento antirretroviral (HAART) no Município de Itanhaem - Estado de São Paulo, 2009-2011 - Dias, Wellington (2013)
Introduction: The use of viral genotyping as a tool for the treatment of HIV positive patients is relevant to review health policies concerning the dispensing of antiretrovirals and contribute to mapping the frequency of HIV virus subtypes in our region. Objective: To identify and characterize the genetic diversity and primary resistance to HIV-1 antiretroviral agents in the city of itanhaem in patients at early stage of treatment . Methods: Cross-sectional study using 50 samples. After extraction and RNA transcription Polymerase Chain Reaction was performed with primers (K1, K2, DP10, F2) which produced fragments of 1200 bp, identified in agarose gel. After purification of PCR products, the fragments were subjected to sequencing reaction. Genetic diversity was analyzed throuh the comparison to the Stanford HIV drug resistance database . Qualitative variables were presented as absolute and relative values. Quantitative variables were presented through their values of central tendency and dispersion. Results: Among the 50 samples, 25 were amplified for analysis of genetic diversity, obtaining results in 13 (52%) female patients and 12 (48%) male patients. Eleven patients (44%) presented mutation in reverse transcriptase with high-level resistance to efavirez ripivirine and 7 patients (28%) presented mutations in the protease with low resistance. Four (16%) recombinant subtypes F / B were found. Conclusion: In the city of Itanhém 52% of the analyzed samples presented acquired resistance. The predominant primary resistance was to NNRTI (11 patients, representing 44%) group; One patient (4%) was found resistant to NRTI group. One patient (4%) was resistant to IP 1 group and one patient (4%) presented resistance to both NRTI and NNRTI groups. We conclude that health policies shoud be implemented considerinG genotyping as a tool to be be offered regionally, respecting the epidemiologic aspects of the disease in each city. A major 10 research concerning the most common subtype of the virus shoud be taken in our region, in order to determine the most effective drugs for antiretroviral therapy.